ANALISIS DIKSI DALAM KUMPULAN PUISI KARYA FIERSA BESARI - Fitri Wulansari; Loselvia; Nayla Nurzalila; Yesmin; Yetri Pelintini Susiharjo; Eti Ramaniyar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the use of diction in the poetry collection written by Fiersa Besari. Diction serves as an essential element of literary works, particularly poetry, since word choice functions not only as a medium for conveying meaning but also as a means of shaping atmosphere, expressing emotion, and strengthening the aesthetic value of a work. Appropriate word selection is capable of representing the poet’s inner experience while emphasizing the message addressed to readers. Based on this perspective, the study focuses on identifying the forms of diction employed, interpreting the meanings reflected through word choice, and examining the role of diction in constructing poetic beauty and depth of meaning.This research applies a qualitative descriptive method supported by a stylistic approach. The data consist of lines, stanzas, and expressions containing diction elements taken from the poetry collection authored by Fiersa Besari. Data collection was conducted through library research, intensive reading, note-taking, and data classification based on diction categories, including connotative words, concrete words, emotive vocabulary, figurative expressions, and symbolic language. Data analysis was carried out by interpreting the contextual meaning of words according to their poetic usage. The findings reveal that the diction employed by Fiersa Besari tends to be simple, poetic, and rich in emotional nuance. Connotative and symbolic expressions dominate the poetic construction, particularly in portraying themes of love, loss, life journeys, and human inner conflict. Furthermore, communicative word choice makes the poems accessible and meaningful without reducing their artistic quality or semantic depth. These findings confirm that the distinctive strength of Fiersa Besari’s poetry lies in the precision of word selection, which effectively builds imagery, evokes atmosphere, and establishes emotional closeness with readers.